2015
DOI: 10.1111/bjd.14241
|View full text |Cite
|
Sign up to set email alerts
|

Skincare products containing low concentrations of formaldehyde detected by the chromotropic acid method cannot be safely used in formaldehyde-allergic patients

Abstract: Our results demonstrate that the low concentrations of formaldehyde often found in skincare products by the CA method are sufficient to worsen an existing dermatitis in formaldehyde-allergic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 35 publications
(87 reference statements)
4
69
1
Order By: Relevance
“…Furthermore, the maximum concentrations of some of the FM I ingredients have been lowered since 2011 according to the IFRA standards. However, despite lower exposure, the situation may be different if products such as scented moisturizers are applied on skin with an existing dermatitis . There were 10 participants with a positive patch test reaction to FM I in 2011 who in 2014 had a negative, irritant or doubtful reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the maximum concentrations of some of the FM I ingredients have been lowered since 2011 according to the IFRA standards. However, despite lower exposure, the situation may be different if products such as scented moisturizers are applied on skin with an existing dermatitis . There were 10 participants with a positive patch test reaction to FM I in 2011 who in 2014 had a negative, irritant or doubtful reaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, this concentration is sufficient to provoke ACD in those allergic to formaldehyde and using these products on healthy skin [18]. It was also shown that these allergic individuals cannot safely use products with low amounts (10–40 ppm) of formaldehyde if they have irritant contact dermatitis, as their dermatitis deteriorates [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Skin cleaning care without washing by water is particularly useful in situations where bathing is impossible (eg, disaster or deterioration of physical condition). However, skin inflammation may occur when using leave‐on products, such as moisturizers, despite the use of lower concentrations of cleaning agents . Therefore, to avoid skin irritation, cleaning agents should be removed from the skin as much as possible.…”
Section: Introductionmentioning
confidence: 99%